GRATITUDE TRAINING TO REDUCE THE DEPRESSION LEVEL AMONG THE PATIENTS WITH CHRONIC KIDNEY FAILURE UNDERGOING THE HEMODIALYSIS THERAPY - Ahmad Fikry Ghazali; Qurotul Uyun; Khairul Anwar Mastor (JIP (Jurnal Intervensi Psikologi), 2023)
ABSTRACT : The purpose of the study was to investigate the effectiveness of gratitude training on reducing depression levels among patients with chronic kidney failure undergoing hemodialysis therapy. The study used a single-subject experimental design with the A-B-A (Baseline A1-Treatment-BaselineA2) format to examine changes in individuals receiving the treatment. Two patients with chronic kidney failure who had undergone hemodialysis therapy for ≤2 years were selected as the participants. The level of depression was measured using Depression Anxiety Stress Scale (DASS)-42 and qualitatively measured through visual inspection. The hypothesis test results supported the effectiveness of gratitude training in reducing the depression level in patients with chronic kidney failure undergoing hemodialysis therapy.